(untitled) (Politeja, 2023)
THE RUSSIAN LANGUAGE STATUS IN POST-SOVIET SPACE: LEGAL STATE – THREATS – PROSPECTS – CHALLENGES For many years of the existence of the Soviet Union, the status of the Russian language was semi-official, although it played a large role in the public space. Only the act on the Languages of the Nations of the USSR of 1990 approved its status as an official language in the entire territory of the USSR. After the collapse of the Soviet Union, its former republics began to shape their own language policies, guided by national interests, considering the current linguistic situation and historical conditions. The effect of these activities was the diversified status of the Russian language (as state, official, inter-ethnic communication, national minority or foreign). The main purpose of the article is to present the differences in the status of the Russian language in the post-Soviet countries, primarily in the formal and legal aspect. An additional question was whether the legal status of the Russian language reflected its actual position in public and social life in the individual countries. The problem continues to be relevant, especially in the context of the foreign policy goals pursued by the Russian Federation and security threats.